Experimental poisoning by Vernonia rubricaulis in sheep. (January 2018) - Godoy, Kelly C.S.; Leal, Paula V.; Araújo, Marcelo A.; Souza, Alda I.; Pott, Arnildo; Lee, Stephen T.; Barros, Claudio S.L.; de Lemos, Ricardo A.A.
Abstract: In order to evaluate the susceptibility of sheep to V. rubricaulis and to establish the clinical signs, serum biochemistry, and pathological findings, eight sheep were fed varying doses of V. rubricaulis . The onset of clinical signs occurred 6–48 h after the ingestion of V. rubricaulis . Clinical courses lasted 6–56 h after the ingestion of the plant. Serum activities of aspartate aminotransferase, gamma-glutamyl transferase, and alkaline phosphatase were highly elevated and glucose blood levels were low in affected sheep. Clinical signs consisted of apathy, anorexia, dry muzzle, respiratory distress, abdominal pain, and mushy feces with streaks of blood and mucus. Two sheep had neurological signs including muscle fasciculation, nystagmus, paddling movements, and blindness. Liver necrosis could be detected antemortem through liver biopsy. Five sheep died and three recovered. The liver was affected in all necropsied sheep; it increased in volume and had marked accentuation of the lobular pattern with red, depressed areas intercalated with a pale yellow network. Ascites and hydropericardium were consistent findings. Microscopically, centrilobular to massive coagulative necrosis was observed. Coagulative necrosis was also observed in a few proximal renal tubules. Microscopic lesions were not found in any other organs. The severity of liver lesions was proportional to the dose. Chemical analysis to detect carboxyatractyloside in V. rubricaulis plant material was negative. It is concluded that V. rubricaulis poisoning in sheep is clinically, biochemically, and pathologically characteristic of an acute hepatoxicosis. Highlights: Sheep are susceptible to poisoning by Vernonia rubricaulis . Experimental poisoning by Vernonia rubricaulis in sheep causes acute hepatotoxicosis. Hepatotoxicity can be demonstrated antemortem by clinical pathology and liver biopsy. Hepatic lesions are dose-dependent.